Literature Review: Pengaruh Terapi Musik terhadap Tekanan Darah Pasien Hipertensi - Adho Alif Akbar; Diah Merdekawati; Lisa Anita Sari (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2022)
Background of Study: Hypertension is one of the main causes of mortality and morbidity in Indonesia, hypertension treatment can be done pharmacologically and non-pharmacologically, to get low side effects, use complementary therapy, namely music therapy in lowering blood pressure, namely classical, Mozart music and instrumental music. This study aims to determine the effect of music therapy on reducing blood pressure. Methods: This study was conducted to collect data on several types of music therapy to lower blood pressure. This research done with collect from several research results to know as much information as possible from data obtained through Google Portal Garuda (IPI), while the research instrument used was observation sheets from journal articles that have been previously researched, namely classical music therapy and insrumental music. Results: Classical music therapy, Mozart music and instrumental music can reduce blood pressure. From the three types og music therapy, classical music therapy was the most effective. If it was done regularly so that music therapy can be used as non-pharmacological therapy to reduce blood pressure, and there was one journal which states that there was no effect of music therapy on effectiveness. Conclusion: Three music therapies that have been compared, the most effective music therapy for lowering blood pressure was classical music therapy. For this reason, it is expected to apply nursing interventions to patients with hypertension by using complementary therapy, namely music therapy.Keywords: Music therapy, hypertension